Implementasi Wakaf Tunai dalam Meningkatkan Stabilitas Ekonomi dan Kesejahteraan Masyarakat di Indonesia - Fanny Muhammad Hanafi; Devi Sofiana Khourin; Evin Hidayanti; Agus Eko Sujianto (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
The findings of the information in this study are useful for understanding the role of cash waqf in creating community welfare and increasing the country’s economic stability. The method used in this study is the literary method with descriptive presentation and qualitative analysis by examining library materials such as books, journals and news on the internet, magazines, articles and other scientific works cited in the proposal. Maintaining the economic stability of a country is not easy. Many of the countries that may be in debt will make the country more developed, but the opposite is true. This will actually make the country even poorer and the level of economic stability will decline. With the existence of cash waqf, the level of poverty can be quickly overcome, even though the impact is not big.